Prevalence of overweight and obesity among Portuguese Youth: a study in a representative sample of 10-18 years old children and adolescents - Sardinha, Luís (2012)
Purpose. The aim of this research was to report the prevalence of overweight and obesity in a representative sample of Portuguese youth. Methods. This was a school-based study performed in Portugal. A total of 22 048 children and adolescents aged 10 – 18 years were included in the study. The World Health Organization (WHO) and the International Obesity Task Force (IOTF) cut-offs were used to categorise overweight and obese participants. Results. Using IOTF cut-offs the prevalence of overweight and obesity was 17.0 and 4.6% in girls, and 17.7 and 5.8% in boys, respectively ( p 0.001 for overweight and p 0.05 for obesity), whereas WHO cut-offs resulted in overweight and obesity prevalence scores of 23.1 and 9.6% in girls, and 20.4 and 10.3% in boys, respectively ( p 0.001 for overweight and p 0.05 for obesity). With IOTF cut-offs, a lower prevalence of obesity and overweight was observed at higher ages, in both genders. With the WHO cut-offs, a lower prevalence of obesity and overweight was observed at higher ages, in boys. In girls, the prevalence of overweight and obesity increases from 10 to 12 years of age and decreases from the age of 13 to 18 years. Conclusion. The prevalence for overweight/obesity among Portuguese children and adolescents vary according to the cut-off points used and are also of concern requiring strategies to promote healthy weight gain among children and adolescents.